2019
DOI: 10.22452/mojem.vol7no1.3
|View full text |Cite
|
Sign up to set email alerts
|

School Level Resources and Students’ Performance in Malaysian National Type Chinese Schools

Abstract: The Malaysian government has always prioritised investment in education by providing quality education as one of the aspirations envisioned in the Malaysian Education Blueprint. Quality education is often associated with better learning environment, adequate resources, and quality teachers. Previous studies in Malaysia were mainly focused on socioeconomic factors that determine students' performance and were consistently focused on students' performance in national schools. This study aims to identify school l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The findings are generalisable to schools that share similar characteristics. For example, it can be generalised across primary schools with a large number of students (Hashim, 2003;Kenayathulla et al, 2019). This is a positive finding in which teachers with positive attitudes were inclined to persist in teaching 21 st century skills despite the barriers faced (Jansen & Merwe, 2015;Razak et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The findings are generalisable to schools that share similar characteristics. For example, it can be generalised across primary schools with a large number of students (Hashim, 2003;Kenayathulla et al, 2019). This is a positive finding in which teachers with positive attitudes were inclined to persist in teaching 21 st century skills despite the barriers faced (Jansen & Merwe, 2015;Razak et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In response, the Malaysian government has always prioritized investment in education by providing quality education as one of its aspirations. In order to achieve quality education, it is often necessary to provide a better learning environment and adequate resources and hire qualified educators (Kenayathulla et al, 2019). Therefore, Islamic religious schools ensure students receive a high-quality education.…”
Section: The Quality Of Religious Schoolmentioning
confidence: 99%
“…In previous studies, several factors have been identified that influence student achievement, such as gender, socioeconomic status, student attitudes, and teacher shortages. The study conducted by Kenayathulla et al (2019) found that factors that determine students' performance include funding, clusters of schools, the number of teachers in schools, small classes, the average income of parents, allocated funds, educational materials, science laboratory facilities, and a lack of teachers and leaders. Therefore, to improve student performance, all of these factors should be addressed in an appropriate manner.…”
Section: Students' Performance In Religious Schoolmentioning
confidence: 99%
“…This inconsistent up-and-down number of students per year in a class may affect student performance as argued by Mishel and Rothstein (2002) among others. Appropriate class size is important for student achievement and in turn can help improve school quality, human capital, and eventually, economic growth (Castelló-Climent & Hidalgo-Cabrillana 2012;Perera & Asadullah 2019;Hanushek 2013;Kenayathulla et al 2019).…”
Section: Introductionmentioning
confidence: 99%